Ростові процеси у стеблі озимої пшениці за різного забезпечення мінеральним живленням - Жук, О.І. (Фактори експериментальної еволюції організмів, 2015)
Aims. The aim of this work was to study the influence of mineral nutrition on stem tissue growth and winter wheat plants productivity. Methods. Winter wheat (Triticum aestivum L.) cultivars ‘Mironivska 808’ and ‘Favoritka’ were grown on mixture of soil and sand in pots with capacity of 7.5 kg. Optimal plant mineral nutrition was N₉₀P₉₀K₉₀ , deficit supply was N₃₂P₃₂K₃₂. During vegetation period the length of stem and fourth and fifth internodes of winter wheat plants were measured. After maturing the internodes and ears length, quantity of grains in ear, and mass of 1000 grains were measured. Results were statistically analyzed with Microsoft Excel. Results. The growth of winter wheat internodes and stem was studied under optimal and deficit support of mineral nutrition main elements — nitrogen, phosphor and potassium. The most intensive growth of wheat was detected in booting phase but under the optimal nutrition it was continued to milky ripeness phase. Under mineral nutrition deficit internodes growth stopped in earing-flowering phase. The smallest internodes were formed in in wheat cv. ‘Favoritka’. Conclusions. It was shown that decreased supply of winter wheat plants of cultivars ‘Mironivska 808’ and ‘Favoritka’ by nitrogen, phosphorus and potassium during pot experiment inhibited growth stem, internodes and productivity of plants.